Biocompatibility assessment of haemodialysis membrane materials by proteomic investigations1. Issue 6 (19th June 2015) - Pieroni, Luisa; Levi Mortera, Stefano; Greco, Viviana; Sirolli, Vittorio; Ronci, Maurizio; Felaco, Paolo; Fucci, Giorgio; De Fulviis, Silvia; Massoud, Renato; Condò, Stefano; Capria, Ambrogio; Di Daniele, Nicola; et al.
<x xml:space="preserve">Abstract</x> We examine and compare the protein adsorption capacity and coagulation profiles of different haemodialysis membrane biomaterials.